Pricing in retail markets with low search costs: Evidence from a price comparison website - Charlie Lindgren; Sven-Olov Daunfeldt; Niklas Rudholm (Institute of Retail Economics (HFI), 2021)
Price comparison websites, where consumers can compare prices at a search cost that is close to zero, have become increasingly common around the world. Using daily information on prices, click-throughs, and the number of retailers for a sample of consumer electronics and durable goods over a period of 62 months, we investigate the effects of the increased use of the Swedish price comparison website PriceSpy on prices and price dispersion. We find that increased use by consumers created potential savings of 290 million SEK in 2016, while increased use by retailers created potential savings of approximately 2.9 billion SEK. Reduced prices due to increased use of the price comparison website thus resulted in total potential consumer savings of nearly 3.2 billion SEK (289 million EUR) for the year 2016 alone. Price comparison websites thus place downward pressure on prices, thereby increasing economic efficiency. We also find that the increased use of the price comparison website by retailers resulted in increased price dispersion, while the effect of more consumers using the website was mixed.
Keywords: D21; D22; D83; L11; L81; 330; Consumer search; price dispersion; information; e-tailing; e-commerce